Statistical Modeling and Optimization of Enzymatic Pretreatment of Empty Fruit Bunches with Laccase Enzyme - Ishmael, Ukaegbu Chinonso; Rashid, Shah Samiur; Jaya Vejayan, Palliah; Mohd Fazli, Farida Asras; Sharifah Suhaiza, Nik Wan Ahmad; Ayodele, Bamidele V. (BioResources, 2016)
Laccase enzyme was used as a pretreatment agent to delignify empty fruit bunches (EFB) for sugar production. The degree of delignification of the biomass was assessed directly by the percentage of pre-pretreatment weight loss (%) after pretreatment and indirectly by the amount of total sugar produced after saccharification of the pretreated biomass with cellulase enzymes. Process parameters such as pretreatment time, temperature, enzyme concentration, substrate concentration, pH, and substrate size were studied using a one-factor-at-a-time (OFAT) analysis. The combined effect of temperature and pH on the pretreatment was studied using the face-centered central composite design (FCCCD) of response surface methodology (RSM). The optimized conditions for EFB pretreatment using laccase enzyme were achieved as follows: sample size, 2 mm; temperature, 25 °C; time, 4 h; substrate concentration, 5% (w/v); pH 5; and enzyme concentration, 20 IU/g of EFB. Although higher pretreatment was achieved with substrates of 1 mm size and at a temperature of 35 °C, these conditions were not considered energetically sustainable because of the need for energy during milling for sample size reduction and energy for temperature maintenance at 35 °C.